WHY I AM CONFUSED TO APPLY MATHEMATICS CONCEPT: STUDENT PERSPECTIVE OF MATHEMATICS ROLE IN LIFE - Sumbaji Putranto; Gamarina Isti Ratnasari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Mathematics is a subject that has many benefits to solve problems in daily life, but many students still confused using mathematical concepts in daily life. This study aims to identify student perspective of mathematics role in daily life, the cause of the student's perspective, and the strategy to overcome the perspective. The study is phenomenological research. The data were collected using interview and questionare The data analysis was done using Bogdan & Biklen approach. The results of the study show that students argue only basic mathematics is used in daily life. The cause of these students' perspective is that students do not feel the mathematical concepts learned at school can be used to solve the problems in daily life and the students are too focused to solve the problem without integrating mathematics in daily life. The strategy used to improve students' perspective are giving students more examples of the use of mathematics in STEM, using contextual based learning models, and providing projects assignment to students related to mathematical applications.